The discovery of human retroviruses and how they cause disease - Gallo, Robert (Henry Stewart Talks, 2007)
Human viruses that cause malignancies, The discovery of human retroviruses, Interspecies transmission of retroviruses, New human viruses/viral diseases, Adult T-cell leukemia caused by HTLV-I, HTLV-I associated diseases, Discovery of HTLV-2, How HTLVs cause disease, Genomic structure of human retroviruses, Mechanism of expression and function of human retroviral gene products, Pathogenic mechanisms of HTLV-I, The discovery of HIV and how it causes AIDS, HIV-1, Some features of HIV pathogenesis, HIV DNA provirus integration into host chromosomal DNA, HIV in cancer
Reviewed at 2017/05/24